Non-covalent functionalization of graphene oxide by pyrene-block copolymers for enhancing physical properties of poly(methyl methacrylate)1. Issue 97 (21st October 2015) - Song, Shiqiang; Wan, Chaoying; Zhang, Yong
<x xml:space="preserve">Abstract</x> Pyrene-functionalized poly(methyl methacrylate)-block-polydimethylsiloxane (Py-PMMA-b-PDMS) copolymers were synthesized via ARGET ATRP method and further used to functionalize GO through the π–π interaction between pyrene and the carbon sheets.